Anxiety and coping mechanisms in facing clinical skills exam: A study among medical student - Qomariyah Nurul; Hidayah Nurul; Al Munawaroh Elsa Hana; Aristiani Windy; Sugiyanti Rina; Sukandar Anis; Annisa; Selohandono Andrianto; Budi Rahayu Ana (BIO Web of Conferences)
The prevalence of mental and emotional health disorders (depression and anxiety) nationally reached 9.8%. Medical students are required to master various competency areas that can cause students to feel pressure and potentially triggering anxiety. The OSCE (Objective Structured Clinical Examination) is an exam that known as a cause of higher anxiety than other exams. This study aims to analyse the factors that influence anxiety during OSCE for medical. This study is qualitative research with a phenomenological approach which aims to reveal and study the phenomena experienced by the subjects. The sample is all active medical students’ class 2019, 2020 and 2021 who fulfil the specified inclusion and exclusion criteria. Data collection methods are Focused Group Discussion (FGD), observation and documentation. We analysed the results of the FGD and interviews using the content analysis method. The results of the research found large categories of research problems, including perceptions and anxiety facing OSCE, factors that cause anxiety during OSCE, and students' coping mechanisms. In dealing with stressors in the form of OSCE students will use two types of coping strategies, problem-focused coping and emotion-focused coping.